2021
DOI: 10.1055/s-0041-1740012
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Singleton Birth Rate during the COVID-19 Lockdown: A Population-Based Study

Abstract: Objective The aim of the study is to evaluate the effect of the coronavirus disease 2019 (COVID-19) pandemic national lockdown period on the rate of singleton preterm births in Israel. Study Design This is a population-based cohort study of 3,41,291 singleton infants born in the months of January to July 2017 to 2020. Multivariable logistic regression analyses were used to estimate the influence of period and year on the rates of preterm births during the lockdown period (11th March − 5th May 2020)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…This is not trivial, as multiple factors at different times during pregnancy might have had an impact on the rate of preterm deliveries. Though there are not, so far, studies available on this interesting topic, we can speculate, in accordance with others, 15,18 that lifestyle and behaviour (more rest, working from home, reduced exposure to other respiratory pathogens) might have contributed to PTB reduction. Other possible pandemic-related changes, which are known to impact on PTB, might have been the adoption of a different and healthier diet, 22 and diminished exposure to air pollution.…”
Section: Discussionsupporting
confidence: 86%
“…This is not trivial, as multiple factors at different times during pregnancy might have had an impact on the rate of preterm deliveries. Though there are not, so far, studies available on this interesting topic, we can speculate, in accordance with others, 15,18 that lifestyle and behaviour (more rest, working from home, reduced exposure to other respiratory pathogens) might have contributed to PTB reduction. Other possible pandemic-related changes, which are known to impact on PTB, might have been the adoption of a different and healthier diet, 22 and diminished exposure to air pollution.…”
Section: Discussionsupporting
confidence: 86%
“…This is not trivial, as multiple factors at different times during pregnancy might have had an impact on the rate of preterm deliveries. Though there are not, so far, studies available on this interesting topic, we can speculate in accordance with others 15,18 that lifestyle and behavior (more rest, working from home, reduced exposure to other respiratory pathogens), might have contributed to PTB reduction. Other possible pandemic-related changes, which are known to impact on PTB, might have been the adoption of a different and healthier diet, 22 and diminished exposure to air pollution.…”
Section: Discussionsupporting
confidence: 87%
“…Our data on a reduction in PTB concomitant with the COVID-19 pandemic period are concordant with those of two recent national-based studies published after the systematic review and meta-analysis of Yang and coll., 9 which concluded that a reduction in the odds of PTB was observed only in single-center studies. The first of these studies was conducted in Israel, 18 on birth data from the Israel national newborn screening program and showed a 10% decline in all preterm deliveries during the COVID-19 pandemic national lockdown period. The second one, in UK, 15 used administrative hospital records and found a slightly lower frequency of preterm birth rates (from 6.1% to 6.0%) during the entire pandemic period compared to pre-lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the number of requests for in utero transfers because of threatened preterm birth and fetal growth restriction decreased during lockdown. Many authors have reported a significant impact of the pandemic, and more specifically, of the different lockdowns on preterm delivery rates and on low-birth-weight births [ 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Most studies show a decrease in the number of preterm births during successive lockdowns.…”
Section: Discussionmentioning
confidence: 99%